Design and analysis of a pneumatic high-impact force drive mechanism for in-pipe inspection robots. (1st October 2016) - Hua, Ye; Konyo, Masashi; Tadokoro, Satoshi
Graphical Abstract: Abstract : A pneumatic actuator is suitable and safe for in-pipe inspection robots in inflammable circumstances because of its ability to withstand explosions. However, ordinary pneumatic actuators limit driving speed because of their slow response. In this paper, we propose a novel pneumatic drive mechanism that can produce a high-impact force to move the in-pipe robot forward with sufficient speed by a catastrophic phenomenon using rapid release between a magnet and springs. We also introduce an anisotropic friction mechanism that uses a self-locking phenomenon to transmit the impact force to the pipe walls efficiently. A pin retraction mechanism that releases the self-locking condition is applied to retrieve the robot from the pipes. Optimizations of the proposed design were conducted based on a motion simulation model and verified in experiments. The experimental results obtained for maximum driving speeds in a straight pipe with different material types were approximately 90 and 50 mm/s for horizontal and vertical pipes, respectively. Stable strokes were also observed at different driving frequencies from 0.5 to 2.0 Hz.